2011
DOI: 10.1121/1.3641399
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-envelope constancy of speech in rooms and the perceptual weighting of frequency bands

Abstract: Three experiments measured constancy in speech perception, using natural-speech messages or noise-band vocoder versions of them. The eight vocoder-bands had equally log-spaced center-frequencies and the shapes of corresponding "auditory" filters. Consequently, the bands had the temporal envelopes that arise in these auditory filters when the speech is played. The "sir" or "stir" test-words were distinguished by degrees of amplitude modulation, and played in the context; "next you'll get _ to click on." Listene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 29 publications
6
23
1
Order By: Relevance
“…They are also consistent with the results of Watkins et al (2011), and demonstrate that the enhancement generalizes to highly variable sentence materials. Taken together, these results may be indicative of mechanisms that compensate for the distortions to the amplitude ENV caused by room reverberation.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…They are also consistent with the results of Watkins et al (2011), and demonstrate that the enhancement generalizes to highly variable sentence materials. Taken together, these results may be indicative of mechanisms that compensate for the distortions to the amplitude ENV caused by room reverberation.…”
Section: Resultssupporting
confidence: 80%
“…The enhancement is not specific to certain syllable continua (Watkins et al, 2011) but generalizes to highly variable speech sentences that are more representative of that encountered in everyday communication situations. In addition, the enhancement process appears to be very rapid-on the order of seconds-and does not show any long-term improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such enhancement is consistent with recent neural data that demonstrate the presence of reverberation-resistant coding of AM in the response properties of single neurons in the inferior colliculus (Delgutte et al, 2012;Kuwada et al, 2012). Because other studies have demonstrated that speech understanding in reverberant soundfields may be modified (Watkins, 2005) or improved (Brandewie and Zahorik, 2010;Srinivasan and Zahorik, 2013) with prior listening exposure to reverberation, and that this effect appears to most strongly influence the processing of the amplitude envelope of the speech signal (Watkins et al, 2011), it is important to determine whether AM sensitivity could be similarly affected by prior listening exposure to reverberation. This is the goal of the present study.…”
Section: Introductionsupporting
confidence: 76%
“…The results suggest that when the auditory system is given prior exposure to a reverberant room, it can compensate for the degrading effects of reverberation. This effect appears to depend critically on the amplitude characteristics of the speech waveform's temporal envelope (Watkins et al, 2011), although the effect has also been demonstrated for non-speech sounds (Watkins and Makin, 2007).…”
Section: Introductionmentioning
confidence: 99%